Cabin crew and international labour contract (decision of the Higher Court of Balearic Islands of February 19, 2021) - Juárez Pérez, Pilar (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
Once again, litigation is being conducted before the Spanish courts as a consequence of the employment relationship that links the airline Ryanair with its workers, this time a cabin crew member. Following in the wake of previous judicial decisions, both the Labour Court and the Superior Court of Justice consider that the labour contract is governed by Spanish law in order to grant greater protection to the worker. For that purpose, the Court carry our a protective interpretation of the clause of choice of law contained in the contract, which initially subjected it to Irish law.
Keywords: cabin crew; international jurisdiction; conflict of laws; law applicable to the international labour contract; illegal assignment of workers